O ficar na adolescência e paradigmas de relacionamento amoroso da contemporaneidade - Justo, José Sterza [UNESP] (Universidade Federal Fluminense, Departamento de Psicologia, 2005)
To stay with someone (ficar) is a quite popular affective type of relationship among teenagers and it is characterized by being brief, fleeting, immediate, fickle and without commitment. Comparative analyses show that to stay with(ficar) follows the same logic which governs fixed ties in other types of relationship. Its particularly provisory and fleeting feature is found, for example, in professional ties in short-term employment, in relationships which were once long-lasting and steady, such as that among neighbours, not to mention family ties. Nowadays, one lives an unprecedented process of time acceleration, space expansion and human rush, which makes it impossible to establish stable and lasting psychosocial ties at all levels of life: from love to work.

O ficar é um relacionamento afetivo bastante popular entre os adolescentes e caracteriza-se por ser breve, passageiro, imediatista, volátil e descompromissado. Análises comparativas demonstram que o ficar obedece à mesma lógica que rege outros relacionamentos. Seu caráter provisório e efêmero está presente, por exemplo, na abreviação dos vínculos empregatícios e na rarefação de relacionamentos outrora sólidos e duradouros tais como os de vizinhança e familiais. Vive-se hoje uma condição de aceleração do tempo, alargamento de espaço e movimentação humana sem precedente, impeditiva de vinculações psicossociais estáveis e prolongadas em todos os planos da vida: do amor ao trabalho.
To stay with (ficar) among teenagers and paradigms of love ties nowadays
Keywords: To stay with; Teenagers; Relationships; Affection; Contemporary world; Ficar; adolescência; Relacionamento; Afetividade; Contemporaneidade